Development of a digital rapid training course for improving the additive manufacturing adoption rate - fused filament fabrication - Van Wageningen, Roelof Pienaar (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.